Knockout of Apolipoprotein E in rabbit promotes premature intervertebral disc degeneration: A new in vivo model for therapeutic approaches of spinal disc disorders. - Anja Beierfuß; Hermann Dietrich; Christian Kremser; Monika Hunjadi; Andreas Ritsch; Thomas Rülicke; Claudius Thomé; Demissew Shenegelegn Mern (PLoS ONE)
Intervertebral disc (IVD) degeneration that accelerates the loss of disc structural and functional integrities is recognized as one of the major factors of chronic back pain. Cardiovascular risk factors, such as deficits of apolipoproteins that elevate the levels of cholesterol and triglycerides, are considered critical for the progress of atherosclerosis; notably in the abdominal aorta and its lumbar branching arteries that supply lumbar vertebrae and IVDs. Obstruction of the lumbar arteries by atherosclerosis is presumed to promote lumbar disc degeneration and low back pain. APOE-knockout rabbits have recently been shown to generate hyperlipidemia with increased levels of cholesterol and triglycerides that mimic the symptoms of atherosclerosis in humans. Here, we analysed IVD degeneration in the lumbar spines of ten homozygous APOE-knockout and four wild-type New Zealand White rabbits of matching age to prove accelerated IVD degeneration in APOE-knockout rabbits, since APOE-knockout rabbits could be a beneficial model for therapeutic approaches of degenerative IVD disorders. Experiments were performed using T1/T2-weighted magnetic resonance imaging, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, glucose-oxidase assay, enzyme-linked immunosorbent assay, quantitative reverse transcription PCR and western blot. APOE-knockout lumbar spines showed more advanced IVD degeneration, obstructed lumbar arteries and lower enhancement of contrast agent in IVDs. Moreover, lower concentration of glucose, lower number of viable cells and lower concentrations of aggrecan, collagen II and higher concentration of collagen I were detected in APOE-knockout IVDs (p < 0.0001). APOE-knockout in rabbits could induce structurally deteriorating premature IVD degeneration that mimics the symptoms of accelerated IVD degeneration in humans. APOE-knockout rabbits could be used as beneficial model, as they can bypass the standard surgical interventions that are commonly applied in research animals for the induction of enhanced IVD degeneration. Their parallel use in therapeutic approaches of IVD disorders and atherosclerosis could reduce the number of research animals to be used and contribute to the principles of 3Rs (Replacement, Reduction and Refinement).